(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
The act of throwing a corrosive whether acid or alkali on another person is termed as Vitriolage. Though sulphuric acid is the most common agent used, a number of other substances may also be utilized. The act is commonly done out of revenge or jealousy towards the other person and is usually not intended to cause death of the victim. The article largely stresses on the legal issues involved in the act of Vitriolage and also deals with the psychological rehabilitation of the victim along with the factors affecting the degree of corrosive burns, signs of corrosive burns and treatment of the victim.